Fatores de risco associados à trombose de artéria hepática: análise de 1050 transplantes de fígado - Pinto, Luís Eduardo Veras (2018)
ABSTRACT Hepatic artery thrombosis (HAT) is an important cause of graft loss and ischemic biliary complications. Its incidence ranges from 2 to 9% in adults, with a mortality rate of up to 55%. The risk factors related to HAT have been related to technical aspects of arterial anastomosis and non-surgical factors. The objective of this study was to evaluate the risk factors for the development of TAH. The sample consisted of 1050 cases of liver transplant performed at the Walter Cantídio University Hospital of the Federal University of Ceará from May 2002 to December 2014. A retrospective and cross-sectional study was carried out, and the variables studied in the donor were: age, degree of steatosis, cause of death and blood group; in the recipient, the variables were: age, gender, MELD, CHILD, warm ischemia time (WIT), cold ischemia time (CIT), liver disease etiology and anastomosis technique. Univariate analysis indicated that the variables related to hepatic artery thrombosis are: calculated MELD (p = 0.04) and WIT (p = 0.005). In the multivariate analysis, age of the recipient ≥42 years (OR = 4.96, 95% CI, 2.26-10.93, p = 0.001), pure MELD ≥14.5 (OR = 2.35, 95% CI, 1.07-5.18, p = 0.034) and warm isquemica time ≥35 minutes (OR = 3.85, 95% CI, 1.43-10.38, p = 0.008) are independent risk factors for TAH. In the prevalence ratio test for analysis of the anastomosis as a variable, it was observed that anastomosis in continuous suture has 263% more chance of thrombosis when compared to interrupted suture (p = 0.018). It is concluded that age> 42 years, WIT ≥35 minutes and pure MELD> 14 are risk factors for TAH. Anastomosis in continuous suture increases risk of TAH when compared to anastomosis with interrupted suture. Keywords: Hepatic artery thrombosis. Risk factors. Liver transplant.